Prevalence of multiple sclerosis in Croatia: data from national and non-governmental organization registries - Benjak, Tomislav (Croat Med J, 2018)
AIM: To update the estimate of multiple sclerosis (MS) prevalence in Croatia using multiple epidemiological tools. METHODS: This level IV, epidemiological study gathered data from three national patient registries and one database of a non-governmental MS patients' organization. Data were extracted on all individuals who had undergone hospital MS treatment, consulted their primary health care providers about MS-related symptoms, been listed as having MS-related disability, or been members of the mentioned non-governmental organization in 2015. A new database was formed, in which all living individuals were identified using a common identification number to prevent double entries. The prevalence rates in 2015 were calculated by age and sex groups. RESULTS: In total, 6160 patients diagnosed with MS were identified (72% women). Most women with MS were 50-59 years old and most men were 40-49 years old. The overall MS prevalence rate was 143.8 per 100 000 population. CONCLUSION: The calculated MS prevalence rate in Croatia in 2015 was more than twice as high as the estimate from 2013. This difference warrants further research into MS epidemiology in Croatia and calls for a rational allocation of funds and human resources to provide adequate care and support to MS patients.